Effect of processing method (natural, washed, honey, fermentation, maceration) on the availability of heavy metals in specialty coffee - Matúš Várady; Jana Boržíková; Peter Popelka (Heliyon, 2024)
The aim of this study was to determine the effect of various methods of processing, such as natural, washed, honey, anaerobic fermentation, and carbonic maceration, on the contents of heavy metals in green and roasted specialty coffees from various countries of origin (Ethiopia, Kenya, Rwanda, Burundi, Guatemala, Nicaragua, and Peru). The heavy metals aluminium (Al), nickel (Ni), chromium (Cr), cadmium (Cd), copper (Cu), and lead (Pb) were identified by a multi-element technique using inductively coupled plasma mass spectrometry. Mercury (Hg) content was determined by atomic absorption spectrometry. The processing method affected the contents of Hg, Al, Ni, Cr, Cd, and Pb in the green and roasted coffees (p < 0.001). Hg content varied in the green coffees processed by fermentation methods vs natural or washed methods (i.e. Rwandan and Guatemalan coffees). Cd content was highest in Guatemalan green coffee processed using carbonic maceration (0.062 mg/kg). Pb content differed between the Ethiopian and Rwandan roasted coffees, with the highest content in the washed method (0.252 mg/kg). The correlations between the contents of Cu and Al, Ni and Cr, and Pb and Cr were significant for both the roasted and green beans. In conclusion, the method of processing can affect the contents of heavy metals in green and roasted specialty coffees. Monitoring heavy metals when processing coffee with new methods, even though further processing such as roasting can substantially reduce their content in some cases, is therefore important.